Inklusivitas Gender dan Kinerja Perusahaan : Studi tentang Peran Kepemimpinan Perempuan dalam Ekonomi Islam di Indonesia - Putri Wulandari; Nurul Huda (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study discusses gender inclusivity in Islamic economics, with a focus on women's leadership roles in Indonesia. The background highlights that although there has been progress in women's participation across various sectors, challenges remain in achieving gender equality in management and leadership. This research aims to explore how the presence of women in leadership positions can influence company performance. Using a qualitative analysis approach and empirical data, the findings reveal that gender inclusivity not only promotes social justice but also positively contributes to innovation and corporate financial performance. These findings underscore the importance of policies that support gender diversity as a strategy for achieving sustainable economic growth in Indonesia. This study contributes to the development of more inclusive corporate governance and highlights the vital role of women in management as a key factor in economic and social sustainability.